The Impact of Motivation and Job Satisfaction on Employee Performance at Maya Sanur Resort & Spa - Sihombing, Irene Hanna H.; Wulandari, Ni Putu Cahyani Trisna; Sulistyawati, Ni Luh Ketut Sri (Journal of Mandalika Review, 2024)
Abstract Introduction: Human resources are a crucial asset for the success of a business, particularly for hotels. The performance of employees significantly influences a company's success; as good employee performance can facilitate the achievement of organizational goals. This study aims to investigate the effect of motivation and job satisfaction on employee performance at Maya Sanur Resort & Spa. Methodology: Using the purposive sampling method, 104 respondents from Maya Sanur Resort & Spa in Bali were selected to participate. A 5-point Likert scale questionnaire containing 32 indicators, was distributed from March to June 2024. The data was analysed using multiple linear regression, t-test, f-test, and coefficient of determination with the SPSS 23 Windows version. Findings: Motivation variable (X1) has a partially positive and significant effect on employee performance, with a t-count greater than the t-table value (3.607 > 1.659) and a significant value of 0.000. Similarly, the job satisfaction variable (X2) has a partially positive and significant effect on employee performance, with a t-count greater than the t-table value (3.324 > 1.659) and a significant value of 0.001. Additionally, the motivation and job satisfaction variables simultaneously have a significant effect on employee performance, with an F-count greater than the F-table value (204.670 > 3.933) and a significant value of 0.000 < 0.05. Conclusion: Motivation and job satisfaction partially or simultaneously have a significant effect on employee performance. This suggests that both motivation and job satisfaction are crucial factors in enhancing employee productivity and overall organizational success. Keywords: Motivation, Job Satisfaction, Employee Performance